Intracellular Trafficking Pathways of Edwardsiella tarda: From Clathrin- and Caveolin-Mediated Endocytosis to Endosome and Lysosome - Sui, Zhi-hai; Xu, Haijiao; Wang, Hongda; Jiang, Shuai; Chi, Heng; Sun, Li (Frontiers in Cellular and Infection Microbiology, 2017)
Edwardsiella tarda is a Gram-negative bacterium that can infect a broad range of hosts including humans and fish. Accumulating evidences have indicated that E. tarda is able to survive and replicate in host phagocytes. However, the pathways involved in the intracellular infection of E. tarda are unclear. In this study, we examined the entry and endocytic trafficking of E. tarda in the mouse macrophage cell line RAW264.7. We found that E. tarda entered RAW264.7 and multiplied intracellularly in a robust manner. Cellular invasion of E. tarda was significantly impaired by inhibition of clathrin- and caveolin- mediated endocytic pathways and by inhibition of endosome acidification, but not by inhibition of macropinocytosis. Consistently, RAW264.7-infecting E. tarda was co-localized with clathrin, caveolin, and hallmarks of early and late endosomes, and intracellular E. tarda was found to exist in acid organelles. In addition, E. tarda in RAW264.7 was associated with actin and microtubule, and blocking of the functions of these cytoskeletons by inhibitors significantly decreased E. tarda infection. Furthermore, formaldehyde-killed E. tarda exhibited routes of cellular uptake and intracellular trafficking similar to that of live E. tarda. Together these results provide the first evidence that entry of live E. tarda into macrophages is probably a passive, virulence-independent process of phagocytosis effected by clathrin- and caveolin-mediated endocytosis and cytoskeletons, and that the intracellular traffic of E. tarda involves endosomes and endolysosomes.